The Confusion – A Perfect Interference Between Competition and Industrial Property - Violeta COJOCARU; Iulian MORARU (Eastern European Journal of Regional Studies)
Industrial property and competition are indissoluble in terms of the legal manner in which the unfair competition act of confusion is committed. The regulation of confusion within the competition legislation of the Republic of Moldova (Law no. 183/2012 on Competition) is in an explicit connection relationship with industrial property, given the fact that the trademarks, industrial designs and other industrial property objects are protected through the provisions of the Law no. 183/2012 on Competition as well. Thus, there is a double protection of industrial property objects: through the rules of industrial property and, at the same time, through those of unfair competition. In the same context, it is important to specify that under competition law are protected even industrial property objects that are not protected under industrial property division law. At the same time, in order to benefit from effective legal protection in accordance with the rules of unfair competition, there is a stringent need for a complex and effective bilateral evidentiary process. In order to validate the theoretical aspects stated above, the practice of the national competition authority of the Republic of Moldova (Competition Council) is essential.